2014
DOI: 10.1016/j.envpol.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate carboxylase as a sensitive protein biomarker for exogenous steroid chemicals

Abstract: a b s t r a c tAssessing protein responses to endocrine disrupting chemicals is critical for understanding the mechanisms of chemical action and for the assessment of hazards. In this study, the response of the liver proteome of male rare minnows (Gobiocypris rarus) treated with 17b-estradiol (E2) and females treated with 17a-methyltestosterone (MT) were analyzed. A total of 23 and 24 proteins were identified with differential expression in response to E2 and MT, respectively. Pyruvate carboxylase (PC) was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…However, the relationship between transcription of mRNA and the abundance of protein is not always direct (Martyniuk et al, 2012b). In the liver of rare minnow after treatment with E2, MT (Liang et al, 2014a), PCP (Fang et al, 2010) and PFOA (Wei et al, 2008a), researchers demonstrated that gene-protein correspondence from data collected with real-time PCR data and 2D gel electrophoresis was highly correlated for some genes and proteins (e.g. fructose-1,6-bisphosphatase; F-1,6-BP, liver fatty acid binding protein; L-FABP, pyruvate carboxylase; PC) but not for others (e.g.…”
Section: Applications Of Toxicoproteomics In Rare Minnow For Endocrinmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the relationship between transcription of mRNA and the abundance of protein is not always direct (Martyniuk et al, 2012b). In the liver of rare minnow after treatment with E2, MT (Liang et al, 2014a), PCP (Fang et al, 2010) and PFOA (Wei et al, 2008a), researchers demonstrated that gene-protein correspondence from data collected with real-time PCR data and 2D gel electrophoresis was highly correlated for some genes and proteins (e.g. fructose-1,6-bisphosphatase; F-1,6-BP, liver fatty acid binding protein; L-FABP, pyruvate carboxylase; PC) but not for others (e.g.…”
Section: Applications Of Toxicoproteomics In Rare Minnow For Endocrinmentioning
confidence: 99%
“…In aquatic toxicology, DIGE and iTRAQ are the most widely used technologies to identify and characterize protein bioindicators of adverse effect (Martyniuk et al, 2012a). Up to now, several toxicological studies based on 2-DE and DIGE approaches have been carried out in rare minnows (Fang et al, 2010(Fang et al, , 2014Liang et al, 2014a;Wei et al, 2008a) (Table 1). Liang et al (2014a) compared the response of the liver proteome of male rare minnows treated with 17β-estradiol (E2) and females treated with 17α-methyltestosterone (MT).…”
Section: Applications Of Toxicoproteomics In Rare Minnow For Endocrinmentioning
confidence: 99%
See 2 more Smart Citations
“…These technologies are broad reaching in medicine, pharmacology, physiology, and environmental science. For ecotoxicology, these approaches have been used to 1) annotate adverse outcome pathways for environmental contaminants [1,2]; 2) characterize chemical modes of action [3,4]; 3) investigate mechanisms of organismal adaptation [5]; and 4) identify candidate biomarkers of exposure [6,7]. In teleost fishes, there are numerous examples of studies that have applied omics technologies to study environmental contaminants, and these most often have included gene expression analysis using microarrays [8,9] and next-generation sequencing (reviewed in Mehinto et al [10] and Wiseman et al [11]).…”
Section: Introductionmentioning
confidence: 99%